HUBUNGAN PAPARAN PESTISIDA DENGAN TEKANAN DARAH DIASTOLIK PADA PETANI HORTIKULTURA DESA KAPUHAN KECAMATAN SAWANGAN KABUPATEN MAGELANG - Siti Nurkhayati; Nurjazuli Nurjazuli; Tri Joko (Jurnal Kesehatan Masyarakat (Undip), 2018)
Cultivated by farmers in Kapuhan Village is horticulture. The results of the preliminary study, the type of pesticide that is widely used is organophosphate class of insecticides which use exceeds the dose. When spraying, farmers also do not use complete personal protective equipment. Hypertension in the Kapuhan Village in 2017 was found as many as 426 cases with a prevalence of 10.02%. The purpose of this study is to determine the relationship of pesticide exposure with diastolic blood pressure to horticultural farmers in Kapuhan Village, Sawangan District, Magelang. This research is an analytic  observational study with a cross-sectional approach. The study was conducted in five hamlets in the Kapuhan Village with a total of 60 respondents determined by the proportional allocation method. Statistical test results showed that there was a relationship on the working period to diastolic pressure (p = 0,000), on the dose variable to diastolic pressure (p = 0.005), as well as the variable storage of pesticides against diastolic pressure ( p = 0.015). There is no correlation between the variable length of work on diastolic pressure (p = 0.145), the frequency of spraying variable on diastolic pressure (p = 0.059), the personal protective equipment variable on diastolic pressure (p = 0.335). From this study it can be concluded that blood pressure is influenced by working period,  pesticide doses, and storage of pesticides. It is recommended to have regular blood pressure checks on farmers by health workers.